Design and fabrication of foldable football goal - Muhammad Hanif, Abd Wahab (2009)
This report presents about football goal that always been used especially in field and soccer court. The usage of a goal is as the posts to shoot the ball trough it. All the ideas of the goal designs and materials are based on the student creativity. The selection for the material that suitable to be used for the foldable goal frame is a material which light in weight, long lasting life and can endure high load. So, the materials that are proposed in this project are mild steel and hinges. In this report will focus more on fabrication of the foldable football goal by using the mechanical machine like welding and grinding machine.